Kajian polusi kendaraan berdasarkan bahan bakar yang dipakai oleh kendaraan di Makassar - Akib, Arif; Basri, Lambang; Thahir, Mukhtar (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Makassar City, as a center for strategic regional development in eastern Indonesia, is experiencing rapid growth in various sectors, including the transportation sector. Economic growth and increasing population have an impact on the increasing number of motorized vehicles in the city. In 2022, the number of motorized vehicles in Makassar was recorded at 1,716 units, and in 2023 it increased to 1,856 units. This increase includes motorized vehicles-passenger cars, buses, trucks, and motorcycles. This study focuses on two main roads, namely Jalan Sultan Alauddin and Jalan Perintis Kemerdekaan, which are primary arterial roads, often used for heavy or long-distance vehicle traffic and have high capacities. This study aims to analyze vehicle volume, levels of CO, NOx, and SOx gas pollution produced, factors that influence differences in exhaust emissions, and solutions to reduce air pollution. The results of the study show that the volume of vehicles on Jalan Perintis Kemerdekaan is higher than on Jalan Sultan Alauddin both in the morning and evening. In the morning, the vehicle volume on Jalan Perintis Kemerdekaan reached 3,830 SMP for LV gasoline, 1,490 SMP for LV diesel, and 5,684 SMP for MC, while on Jalan Sultan Alauddin 3,397 SMP for LV gasoline, 917 SMP for LV diesel, and 4,882 SMP for MC. CO gas emissions were mostly produced by LV gasoline-fueled vehicles, followed by motorcycles. NOx gas was mostly produced by light vehicles powered by gasoline and diesel, while SOx was mostly produced by light vehicles powered by diesel. Factors that influence differences in exhaust emissions include vehicle age, fuel type, and vehicle maintenance. The proposed solution to reduce air pollution is to plant trees that can absorb pollution in the air. This study underlines the importance of vehicle emission management to maintain air quality in urban areas..